FA03.05: NEOADJUVANT CHEMOTHERAPY OR CHEMORADIOTHERAPY FOR ADENOCARCINOMA OF THE ESOPHAGUS. (14th September 2018) - Visser, Els; Edholm, David; Smithers, Mark; Thomson, Iain; Burmeister, Bryan; Walpole, Euan; Gotley, David; Joubert, Warren; Atkinson, Victoria; Mai, Tao; Thomas, Janine; Barbour, Andrew
Abstract: Background: Multimodality treatment of patients with esophageal adenocarcinoma (EAC) improve survival, but the optimal treatment strategy remains undetermined. The aim of this study was to compare outcomes in patients undergoing neoadjuvant chemotherapy (nCT) and neoadjuvant chemoradiotherapy (nCRT) for EAC. Methods: Patients who underwent nCT or nCRT followed by surgery for EAC were identified from a prospective database (2000–2017) and included in this study. After propensity score matching, we compared the impact of the treatments on postoperative complications, in-hospital mortality, pathological outcomes and survival rates. Results: Of the 396 eligible patients, 262 patients were analysed following propensity score matching. This resulted in 131 patients in the nCT group versus 131 patients in the nCRT group. There were no significant differences between the nCT and nCRT groups for overall complications (59% vs 57%, P = 0.802) or in-hospital mortality (2% vs 0%, P = 0.156). Patients who had nCRT had more R0 resections (93% vs. 83%, P = 0.013), and a higher pathological complete response rate (15% vs. 5%, P < 0.001). The pattern of recurrence was similar ( P = 0.753) and there were no differences in 5-year disease-free survival rates (nCT vs nCRT; 39% vs 39%, P = 0.879) or 5-year overall survival rates (nCT vs nCRT; 44% vs 33%, P = 0.645). Conclusion: In this study no differences between nCT and nCRT were seen in postoperative complications and in-hospital mortality in patients treated for EAC. Inspite of improved complete resection and pathological response there was no difference in the overall survival between the treatment modalities. Disclosure: All authors have declared no conflicts of interest.